Formulation and Evaluation of Combined Floating Bilayer Tablet of Metformin, Pioglitazone and Glimepiride - Tiwari, Akhilesh (International Journal of Pharmaceutical & Biological Archive, 2022)
The objective of present investigation was to design the concept of hydro dynamically balanced bilayered tablet containing glimepiride and pioglitazone hydrochloride as immediate release layer and metformin hydrochloride as sustain release floating layer. Floating layer of metformin hydrochloride was prepared by employing different grades of gel forming agent and by various gas generating agent. The floating tablets were evaluated for uniformity of weight, hardness, friability, drug content, in vitro buoyancy, swelling index and dissolution studies. The prepared tablets exhibited satisfactory physico-chemical characteristics. All the prepared batches showed good in vitro buoyancy. The tablet swelled radially and axially during in vitro buoyancy studies. It was observed that the tablet remained buoyant for 12 hours. The drug release from the tablets was sufficiently sustained.